Circuits, the everyday and international relations: Connecting the home to the international and transnational. (June 2019) - Mac Ginty, Roger
The primary aim of this article is methodological. It proposes circuitry as an analytical device – not a mere metaphor – as a way of connecting the everyday and the hyper-local to the national, international, transnational and all levels in between. Thus, the article is concerned with international relations' perennial levels of analysis problem. The study is prompted by empirical research from the Everyday Peace Indicators project in which research subjects narrated their own (in)security in terms of the home and the immediate vicinity of the home. The home can be regarded as a key part of everyday and ontological security for many people, but how do we connect this to the international and transnational? The article draws on the literature on engineered and biological circuits in order to propose a novel analytical device with which to emphasise the connectivity between apparently unconnected levels. A life history is used to illustrate how the analytical device might be operationalised.